REVITALIZING ILM AL-KALAM IN ISLAMIC EDUCATION: ‎FOSTERING CRITICAL REASONING AMID THE CRISIS OF ‎RELIGIOUS RATIONALITY ‎ - Hidayat, Muhammad; Samad, Duski; Mamad, Firdaus; Fadly, Ahmad (International Journal of Multidisciplinary Reseach, 2025)
The crisis of rationality and the decline of critical thinking among students have become urgent challenges in contemporary Islamic education. Phenomena such as blind obedience to religious figures, emotional fanaticism in public discourse, and the lack of reflective reasoning among learners indicate the need for a reorientation of Islamic educational paradigms. This article aims to revitalize the function of Ilm al-Kalam as the foundation for strengthening rationality and theological consciousness within Islamic education. Using a qualitative-descriptive approach and a review of classical and contemporary literature, this study explores the rational, argumentative, and ethical dimensions of Ilm al-Kalam that can be integrated into the curriculum and learning process of Islamic Religious Education (PAI). The findings reveal that applying the principles of Ilm al-Kalam fosters critical thinking, reasoned faith, and a balanced understanding of creed in the modern socio-religious context. The revitalization of Ilm al-Kalam thus represents not only theological reinforcement but also an epistemological transformation toward a rational, dialogical, and civilized Islamic education.